Development of Interactive Learning Content Based on Blended Learning in the Implementation of the Independent Curriculum for Science Subjects at SDN 4 Abuan - Putra, I Ketut Dedi Agung Susanto; Ni Luh Sri Arta Ningsih (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2023)
The delivery of science subject matter still uses the lecture method and learning content only comes from static reading sources such as learning modules without interaction, causing obstacles in the learning process. This study aims to produce and implement and describe the responses of teachers and students to the development of interactive content for science subjects with a blended learning strategy at SDN 4 Abuan. The method used in this study is research and development with the ADDIE development model, namely analyze, design, development, implementation and evaluation. The subjects of the study were grade VI students of SDN 4 Abuan. Based on the stages that have been passed, an interactive learning content product using Articulate Storyline 3 technology with a blended learning strategy was distributed through the Google Classroom LMS with the acquisition of an average coefficient of validity of content experts and media experts of 1.00 in the "Very Valid" criteria. For the effectiveness of the product get an N-Gain of 0.91 with the criteria "Effective". In addition, the average results of student and teacher response scores were 68.9 and 47 with the criteria of "Very Positive".